New Method for Beat-to-Beat Fetal Heart Rate Measurement Using Doppler Ultrasound Signal - Kupka, Tomasz; Matonia, Adam; Jezewski, Michal; Jezewski, Janusz; Horoba, Krzysztof; Wrobel, Janusz; Czabanski, Robert; Martinek, Radek (Sensors (Basel, Switzerland), 2020)
The most commonly used method of fetal monitoring is based on heart activity analysis. Computer-aided fetal monitoring system enables extraction of clinically important information hidden for visual interpretation-the instantaneous fetal heart rate (FHR) variability. Today's fetal monitors are based on monitoring of mechanical activity of the fetal heart by means of Doppler ultrasound technique. The FHR is determined using autocorrelation methods, and thus it has a form of evenly spaced-every 250 ms-instantaneous measurements, where some of which are incorrect or duplicate. The parameters describing a beat-to-beat FHR variability calculated from such a signal show significant errors. The aim of our research was to develop new analysis methods that will both improve an accuracy of the FHR determination and provide FHR representation as time series of events. The study was carried out on simultaneously recorded (during labor) Doppler ultrasound signal and the reference direct fetal electrocardiogram Two subranges of Doppler bandwidths were separated to describe heart wall movements and valve motions. After reduction of signal complexity by determining the Doppler ultrasound envelope, the signal was analyzed to determine the FHR. The autocorrelation method supported by a trapezoidal prediction function was used. In the final stage, two different methods were developed to provide signal representation as time series of events: the first using correction of duplicate measurements and the second based on segmentation of instantaneous periodicity measurements. Thus, it ensured the mean heart interval measurement error of only 1.35 ms. In a case of beat-to-beat variability assessment the errors ranged from -1.9% to -10.1%. Comparing the obtained values to other published results clearly confirms that the new methods provides a higher accuracy of an interval measurement and a better reliability of the FHR variability estimation.
Keywords: fetal heart rate; Electrocardiography; Fetal Monitoring; Heart Rate; Pregnancy; Doppler ultrasound signal; těhotenství; srdeční frekvence; reprodukovatelnost výsledků; Reproducibility of Results; analýza dat; beat-to-beat variability; fetal monitoring; srdeční frekvence plodu; lidé; ženské pohlaví; Humans; Heart Rate, Fetal; ultrasonografie dopplerovská; monitorování plodu; Female; Data Analysis; Ultrasonography, Doppler; elektrokardiografie